Development and emerging trends of drug resistance mutations in HIV: a bibliometric analysis based on CiteSpace - Chen, Xuannan; Chen, Xi; Lai, Yu (Frontiers in Microbiology, 2024)
Background: Antiretroviral therapy has led to AIDS being a chronic disease. Nevertheless, the presence of constantly emerging drug resistance mutations poses a challenge to clinical treatment. A systematic analysis to summarize the advancements and uncharted territory of drug resistance mutations is urgently needed and may provide new clues for solving this problem.We gathered 3694 publications on drug resistance mutations from the Web of Science Core Collection with CiteSpace software and performed an analysis to visualize the results and predict future new directions and emerging trends. Betweenness centrality, count, and burst value were taken as standards.The number of papers on HIV medication resistance mutations during the last ten years shows a wave-like trend. In terms of nation, organization, and author, the United States (1449), University of London (193), and Mark A. Wainberg (66) are the most significant contributors. The most frequently cited article is "Drug resistance mutations for surveillance of transmitted HIV-1 drug-resistance: 2009 update." Hot topics in this field include "next-generation sequencing," "tenofovir alafenamide," "children," "regimens," "accumulation," "dolutegravir," "rilpivirine," "sex," "pretreatment drug resistance," and "open label." Research on drug resistance in teenagers, novel mutation detection techniques, and drug development is ongoing, and numerous publications have indicated the presence of mutations related to current medications. Therefore, testing must be performed regularly for patients who have used medications for a long period. Additionally, by choosing medications with a longer half-life, patients can take fewer doses of their prescription, increasing patient compliance.This study involved a bibliometric visualization analysis of the literature on drug resistance mutations, providing insight into the field's evolution and emerging patterns and offering